Spatial Policy Regarding Carbon Trading for Climate Change Mitigation in Indonesia: Environmental Justice Perspective - Firmandayu, Nilam; Abdalrhman, Ayman Alameen Mohammed (Journal of Law, Environmental and Justice, 2025)
Environmental protection assurances in spatial plans for carbon trading zones have not been stringently enforced despite their comprehensive overlap with carbon absorption areas in forested regions.  This study examines deficiencies in legal rules to offer solutions for equitable policy frameworks in climate change mitigation.  The research is normative and employs a statutory method.  This research indicates three legal issues associated with the legal vacuum: the absence of regulation concerning the classification of strategic carbon zones and the jurisdiction of pertinent organizations.  Secondly, recommendations for policy direction include the formulation of strategic carbon zoning provisions within the Spatial Planning Law, the incorporation of carbon zoning regulations into regional spatial plans, and the draughting of a revision to Presidential Regulation Number 98 of 2021 in collaboration with policymakers concerning special delegation to relevant institutions.  This paper offers an overview of the spatial policy model for carbon trading within the environmental justice and climate change mitigation framework.